The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1159/000490822
|View full text |Cite
|
Sign up to set email alerts
|

Qiliqiangxin Rescues Mouse Cardiac Function by Regulating AGTR1/TRPV1-Mediated Autophagy in STZ-Induced Diabetes Mellitus

Abstract: Background/Aims: To explore the potential role of qiliqiangxin (QLQX) A traditional Chinese medicine and the involvement of angiotensin II receptor type 1 (AGTR1) and transient receptor potential vanilloid 1 (TRPV1) in diabetic mouse cardiac function. Methods: Intragastric QLQX was administered for 5 weeks after streptozotocin (STZ) treatment. Additionally, Intraperitoneal injections of angiotensin II (Ang II) or intragastric losartan (Los) were administered to assess the activities of AGTR1 and TRPV1. Two-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…All these results suggested that autophagy at the end of myocardial injury would be excessively activated to overconsume proteins and organelles in cells in the model of ISO-induced myocardial injury, while QLQX treatment could normalization of autophagic processes to play the role of cardioprotection. It was noteworthy that the effect of QLQX on the regulation of autophagy was not in line with the result of Tong et al (2018). In Tong et al’s experiment, it suggested that the level of autophagy was activated by QLQX in the CHF rats induced by STZ.…”
Section: Discussionmentioning
confidence: 91%
“…All these results suggested that autophagy at the end of myocardial injury would be excessively activated to overconsume proteins and organelles in cells in the model of ISO-induced myocardial injury, while QLQX treatment could normalization of autophagic processes to play the role of cardioprotection. It was noteworthy that the effect of QLQX on the regulation of autophagy was not in line with the result of Tong et al (2018). In Tong et al’s experiment, it suggested that the level of autophagy was activated by QLQX in the CHF rats induced by STZ.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, a study has shown that QLQX improves autophagy via TRPV-1 dependent mechanism in the diabetic heart (9). It also showed that QLQX treatment improves cardiac function and myocardial phenotype in the diabetic mouse model (96). To add to that, QLQX improves endothelial aortic function in diabetic rats via RAS and NO pathways; by inhibiting the expression of ACE and AT-1, and by regulating the NO balance (97).…”
Section: Antioxidants and Anti-inflammatory Approaches To Treat Diabetes-induced Cardiorenal Syndromementioning
confidence: 98%
“…Equally as important to recognize is that DM affects multiple systems of the body [3,10,12,[22][23][24][25]. DM has been tied to mental illness [26,27], vascular brain injury [7,[28][29][30][31][32], cardiovascular disease, immune function , and stem cell regulation [7,[32][33][34][35][36].…”
Section: Metabolic Disease Diabetes Mellitus and Dementiamentioning
confidence: 99%